Global versus local processing: seeing the left side of the forest and the right side of the trees - Christie, John; Ginsberg, Jay P.; Steedman, John; Fridriksson, Julius; Bonilha, Leonardo; Rorden, Chris (Frontiers in Human Neuroscience, 2012)
Previous studies using hierarchical figures (where a large global shape is composed of a series of smaller local shapes) suggest that performance is better for local features presented in the right relative to left visual field, whereas the opposite pattern is observed for global features. These findings have been interpreted as demonstrating that the left hemisphere is biased for local features, while the right hemisphere preferentially processes global features. However, these effects have proved small in healthy adults. Further, data from neurological patients suggests that local deficits may be allocentric (e.g. following left hemisphere injury, individuals are relatively slow to detect features on the right side of an object, regardless of visual field). Here we investigate these effects in healthy adults. Specifically, on each trial we presented two hierarchical figures (one in each hemifield), but crucially the left and right side of each item were composed of different local features. We observed that both neurologically healthy individuals, as well as an individual with brain injury, were relatively worse detecting local information on the right side of objects, regardless of spatial location. This work is consistent with recent work in neurological patients, and provides a new paradigm for exploring hemispheric specialization.